Implementation of Minister of Trade Regulation Number 40 of 2022 concerning Prohibition of Trade in Imported Used Clothing in the City of Surakarta - Hermawan, Risma Dewi; Prastyanti, Rina Arum; Santoso, Aris Prio Agus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Fulfilling the need for decent clothing, the price and quality differ between used clothes and new clothes, so that business actors provide clothing needs with quality models but at affordable prices, so thrifting businesses emerge where this business sells used clothes. The development of the used clothing trade is clearly visible at the moment, one of the places selling used clothes in Surakarta that is well known to many people is the Tirtonadi Convention Hall. However, there is another side, business actors only prioritize profits, thereby ignoring public health problems. The problem in this research is the implementation of Minister of Trade Regulation Number 40 of 2022 concerning Trade in Imported Used Clothing in the City of Surakarta, whether it has been implemented well or not. This type of research is empirical research. Data collection techniques were carried out by interviews at the research location. The results of the research show that the implementation of Minister of Trade Regulation Number 40 of 2022 concerning Trade in Imported Used Clothing in the City of Surakarta has not run optimally due to lack of supervision and law enforcement, lack of education and outreach, economic dependence, availability and quality of local products, inadequate bureaucratic structure. efficient.